High-temperature quantum spin Hall insulator in compensated n-p codoped graphene. (28th January 2016) - Yang, Yingping; Qi, Shifei; Xu, Xiaohong
Abstract: The quantum spin Hall effect (QSH) has been experimentally observed in some quantum wells. However, an ultralow temperature due to an extremely small band gap severely limits its potential application in dissipation-less quantum electronics. Using first-principles calculations, we present a novel kinetic pathway for realizing a high-temperature QSH insulator by n-p codoping of graphene. Our results show that a large and intrinsic band gap of about 26.9 meV, making it viable near room-temperature application, can be achieved via compensated n-p codoping, e.g. doping both thallium (Tl) and tetrafluorotetracyanoquinodimethane (F4-TCNQ) into graphene. In addition, the band gap of the Tl/graphene/F4-TCNQ system is tunable using the Tl doping concentration. This study provides a new solution for experimental studies and practical applications of the high-temperature QSH effect.